HEART RATE VARIABILITY IN WOMEN WITH IDIOPATHIC INFERTILITY BEFORE AND AFTER PSYCHOCORRECTION - V. A. Krutova; T. G. Melkonyanc (Кубанский научный медицинский вестник, 2014)
The psychocorrection was carried with 70 women with idiopathic form of infertility. Before and after psychocorrection was performed registration of heart rate variability. Retrospectively, according to the results of psychocorrection, the examined women with idiopathic infertility were divided into three groups. The first group consisted of the women, in the case of which the first course of psychocorrection was effective. After psychocorrection, there was increase in the variability of the heart rhythm (D increased by 129,2%, V% - 35,7%, rMSSD - 48,8%, PNN 50% - 47,4%, Mo - 5,2%, TR, - 6%). The second group consisted of the women, which became pregnant and gave childbirth after the second or the third course of psychocorrection. After the first course of treatment is a slight increase in the variability of the heart rhythm (D, V% was not significantly changed. PNN50% increased by 18,9%, 5,6% - Mo, TR - 46,0%). The third group consisted of the women, in the case of which the used methods were ineffective. Heart rate variability parameters were not significantly changed. Therefore the dynamics parameters of heart rate variability may be indicative of the effectiveness of psycho-correction in women with idiopathic infertility.